2019
DOI: 10.7160/aol.2019.110401
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Computing in Precision Agriculture: A Systematic Review

Abstract: The applications of ubiquitous computing have increased in recent years, especially due to the development of technologies such as mobile computing and its integration with the real world. One of the challenges in this area is the use of context sensitivity. In agriculture, this can be considered as the context related to the environment, such as the chemical and physical aspects that characterize the different soil types. This scenario periodically changes due to factors such as climate, type of cultivar and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The information may have different purposes such as detecting plant species(Kumar et al, 2016), bird species(Fiehn et al, 2018), plant size (Joshi et al, 2017),(Fukatsu, 2014), fruit color(Tan et al, 2016), plagues on fruits(Tan et al, 2016) and also to count insects(Fukatsu, 2014). These applications show the potential in the area because of the diversity of information that can be obtained with the same equipment Helfer et al (2019). showed that studies already used large amounts of Wireless Sensors Networks (WSN) this aspect was also detected in this mapping.…”
mentioning
confidence: 99%
“…The information may have different purposes such as detecting plant species(Kumar et al, 2016), bird species(Fiehn et al, 2018), plant size (Joshi et al, 2017),(Fukatsu, 2014), fruit color(Tan et al, 2016), plagues on fruits(Tan et al, 2016) and also to count insects(Fukatsu, 2014). These applications show the potential in the area because of the diversity of information that can be obtained with the same equipment Helfer et al (2019). showed that studies already used large amounts of Wireless Sensors Networks (WSN) this aspect was also detected in this mapping.…”
mentioning
confidence: 99%